The importance of the maqasid al-shari'ah in the process of governing and policy making - Omar, Anwar Fakhri; Mohd Nor, Amir Husin; Alias, Muhammad Nazir; Samsudin, Mohd Adib; Ibrahim, Ibnor Azli; Laluddin, Hayatullah; El-Seoudi, Abdel Wadoud Moustafa Moursi; Muhammad Husni, Ahmad (American-Eurasian Network for Scientific Information (AENSI Publisher), 2012)
Muslim jurists, in order to ensure that all the policies drawn by the authority are in line and consistent with the principles and foundations of Islam, provided some guidelines which have to be followed in the process of drafting relevant rules and regulations. Beside awareness of these guidelines, it is also necessary to have a thorough knowledge of the maqasid al-shari‘ah and the manner of their application. Therefore, this article attempt to analyze the significance of maqasid al-shari‘ah (purposes of the law) in the area of siyasah shar‘iyyah (Islamic public policy). This study using both descriptive and analytical methods, concludes that maqasid al-shari‘ah (purposes of the law) are extremely important, therefore they should be seriously taken into consideration in the process of formulation of public policies and administrative law. Attention should also be given in the process to the level of maqasid in determing their priorities.